Vaccination rates and COVID-19 outcomes across US states - Robert J. Barro (American Enterprise Institute (AEI), 2022)
Rates of COVID deaths, hospitalizations, and cases differ markedly across U.S. states, as do rates of vaccination. This study uses cross-state regressions to assess impacts of vaccinations on COVID outcomes. A number of familiar issues arise concerning cross-sectional regressions, including omitted variables, behavioral responses to vaccination, and reverse causation. The benefits from a field context and from the broad range of observed variations suggest the value from dealing with these issues. Results along these lines reveal sizable negative effects of vaccination on deaths, hospitalizations, and cases up to early December 2021, although vaccine efficacy seems to wane over time. The estimates imply that 250 additional doses, with a marginal cost around 40000, leads to one expected life saved. This 40000 is far below typical estimates of the value of a statistical life. Results since December 2021 suggest smaller effects of vaccinations on deaths and, especially, hospitalizations and cases. These findings may reflect diminishing effectiveness of vaccines against new forms of the virus, notably the omicron variant. A further possibility is that confidence engendered by vaccinations may have motivated individuals and governments to lessen non-pharmaceutical interventions, such as masking and social distancing.
Keywords: A; 330; Coronavirus; Health Care Policy; Vaccines